Persepsi Orang Tua Terhadap Pentingnya Pendidikan Bagi Anak Usia Dini Pada Masyarakat Suku Bajo Desa Kalupapi Kecamatan Bangkurung Kabupaten Banggai Laut - Kartika Rajung; Nurhayati Tine; Icam Sutisna; Waode Eti Hardiyanti (Student Journal of Early Childhood Education, 2022)
The purpose this study was to determine the parent’s perception of the importance of education for early childhood in the bajo tribal community, kalupapi village bangkurung district banggai laut regency and the role of the village government in facilitating infrastructure completeness. This research is a qualitative research with qualitative descriptive method and uses interview and documentation data collection techniques as well as triangulation. The subjects this study consisted of five informants, namely parents, teacher and the village government, the results of this study indicate the parents perception of education are very important, this can be seen from the result interview which the show that parents understanding of early childhood education is staring to change. People know that early childhood education is the best means of increasing children’s growth an development. Lack of adequate infrastructure facilities resulting in less effective learning. However, this does not reduce the enthusiasm of the children in going to school and motivation of parents who are so great for the success of their children. Keywords: community perception,bajo tribe,early childhood educatio